Reactive construction of catalytic carbonization system in PP/C60/Ni(OH)2 nanocomposites for simultaneously improving thermal stability, flame retardancy and mechanical properties. (February 2020) - Wen, Xin; Min, Jiakang; Tan, Haiying; Gao, Doudou; Chen, Xuecheng; Szymańska, Karolina; Zielińska, Beata; Mijowska, Ewa; Tang, Tao
Graphical abstract: Abstract: It is a great challenge to fabricate polymer nanocomposites with synchronously improved comprehensive performances. Herein fullerene (C60 ) and nickel hydroxide (Ni(OH)2 ) were reactively modified by grafting of polypropylene (PP) chains, then they were added into PP matrix to construct a catalytic carbonization system. The resultant PP nanocomposites exhibited simultaneous improvements on thermal stability, flame retardancy and mechanical properties. The enhanced mechanism on thermal properties was mainly ascribed to the synergistically catalytic carbonization effect of C60 /Ni(OH)2 on delaying the thermal decomposition of PP and forming better carbon layer during combustion. Besides, the trapping radicals of C60 and 3D network structure of nanofillers also were helpful to improve their flame retardancy. Moreover, the improvement on mechanical performances with balanced stiffness and toughness resulted from good dispersion of nanofillers and strong interfacial adhesion between nanofillers and polymer matrix. This work provided a facile and efficient strategy for designing and fabricating high-performance polymer nanocomposites.